Cascaded Phase-Preserving Amplitude Regeneration in a DPSK Transmission System - Schmauß, Bernhard; Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Leuchs, Gerd (ECOC 2009, Vienna, Austria, 20-24 September, 2009)
Experimental results obtained on 10 Gb/s RZ-DPSK transmission in a recirculating fiber-loop setup show that nonlinear amplifying loop mirrors can efficiently enhance system performance. Main limiting factor is amplified Rayleigh backscattering in highly nonlinear fiber. © VDE VERLAG GMBH.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.cascad